Special paperReconstruction of the left-sided brachiocephalic trunk after vascular ring operation in left-handed child with Kommerell’s diverticulum - Haponiuk, Ireneusz; Paczkowski, Konrad; Chojnicki, Maciej; Jaworski, Radosław; Steffens, Mariusz; Szofer-Sendrowska, Aneta; Kwaśniak, Ewelina; Zieliński, Jacek; Gierat-Haponiuk, Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of a 2-year-old girl with prenatal diagnosis of vascular ring composed of a right-sided aortic arch, a left ligamentum arteriosum, and a left subclavian artery (arteria lusoria sin) originating from a retroesophageal Kommerell’s diverticulum, who was referred for surgery with symptoms related to local compression – severe dysphagia and respiratory disorders. Through the left posterolateral thoracotomy, a ligamentum arteriosum between the Kommerell’s diverticulum and the left pulmonary artery was divided and because of left-handedness of the child a brachiocephalic trunk was reconstructed in the fashion of anastomosis of the left subclavian artery and the left common carotid artery, originating from the ascending aorta.